2009
DOI: 10.1007/s12031-009-9178-7
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Molecular Evolution of the Neuropeptide Pituitary Adenylate Cyclase-Activating Polypeptide (PACAP) and its Receptors in the Lizard Podarcis sicula (Squamata, Lacertidae)

Abstract: The presence of the pituitary adenylate cyclase-activating polypeptide (PACAP) and its receptors PAC(1), VPAC(1), and VPAC(2) was studied in the lizard Podarcis sicula gastrointestinal and respiratory tissues. The expression and distribution of this neuropeptide was investigated using RT-PCR, immunohistochemistry, and in situ hybridization techniques. RT-PCR showed that several tissues of this reptile synthesize an mRNA encoding for PACAP. Performing in situ hybridization and immunohistochemistry, we found a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In reptiles, few members of this family have been reported to date. A VIP and GCG peptides were isolated from the Alligator mississippiensis , the nucleotide precursor of the latter peptide reported from the Heloderma suspectum [ 28 - 30 ] and a PRP/PACAP mRNA was recently characterised from the Italian wall lizard Podarcis sicula [ 31 , 32 ]. Sequence database searches on the lizard Anolis carolinensis genome identified for the first time the genes encoding the reptile PHI/VIP (ENSACAG00000005619), PRP/PACAP (ENSACAG00000008729), GHRH (ENSACAG00000011836), GCG/GLP (ENSACAG00000014182) and GIP (ENSACAG00000006291) (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In reptiles, few members of this family have been reported to date. A VIP and GCG peptides were isolated from the Alligator mississippiensis , the nucleotide precursor of the latter peptide reported from the Heloderma suspectum [ 28 - 30 ] and a PRP/PACAP mRNA was recently characterised from the Italian wall lizard Podarcis sicula [ 31 , 32 ]. Sequence database searches on the lizard Anolis carolinensis genome identified for the first time the genes encoding the reptile PHI/VIP (ENSACAG00000005619), PRP/PACAP (ENSACAG00000008729), GHRH (ENSACAG00000011836), GCG/GLP (ENSACAG00000014182) and GIP (ENSACAG00000006291) (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although PACAP had greater potency than VIP to stimulate cAMP, the two peptides did not have additive effects when applied simultaneously, suggesting that they act on the same receptors (Guijarro et al 1995). Less studies have shown the presence of the peptide itself in the liver: PACAP and its mRNA are present in the liver of the lizard Podarcis sicula (Valiante et al 2009) and PACAP immunoreactivity has been found in the liver of the developing zebrafish (Mathieu et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The sequence was analyzed for similarity with BLASTn program (http://www.ncbi.nlm.nih.gov/). Protein translation was done using Genamics Expression 1.1 software (Valiante et al, , ). Putative protein molecular weight was analyzed using the tools from ExPASy Molecular Biology Server (http://www.expasy.org/).…”
Section: Methodsmentioning
confidence: 99%